State, BUMN (State Owned Enterprises - SOEs) and Role of Law in Economic Development: A Theoretical Approach - Teuku Syahrul Ansari (Britain International for Academic Research (BIAR) Publisher, 2019)
In developing the Business Judgment System for State-Owned Enterprises (SOEs, Persero) in Indonesian Economic Law, it is necessary to elaborate on the theory of the role of law in economic development. According to J.D. Mrs. Hart has three elements that must be developed in the legal system so that the law plays a role in economic development, namely predictability, stability, justice (fairness). The role of the law, basically refers to the main purpose of the law, which is to create an orderly society. Order and balance in society need to be achieved, so that human interests will be protected in achieving their goals. In general, the law functions to divide rights and obligations, regulate how to solve legal problems and maintain legal certainty. The role of the law basically refers to the main objective of the law, which is to create an orderly society. Order and balance in society need to be achieved, so that human interests will be protected in achieving their goals. In general, the law functions to divide rights and obligations, regulate how to solve legal problems and maintain legal certainty. The focus of this paper is the interaction of Indonesian corporate law in the Indonesian Economic Law system in the management of state-owned enterprises, as one of the corporations with legal status to be able to compete globally, because this principle is a universal principle. Corporate law and globalization interact in the same social space and interests. With these interactions, it allows various possibilities, such as integration, incoordination (partial merging), competition (each running alone), conflict (conflicting), and avoidance (one of the laws avoids the enforcement of other laws).